THER-24. TARGETED RADIOIMMUNOTHERAPY FOR EMBRYONAL TUMOR WITH MULTILAYERED ROSETTES. (23rd April 2019) - Bailey, Kayleen; Pandit-Taskar, Neeta; Humm, John; Zanzonico, Pat; Gilheeney, Stephen; Cheung, Nai-Kong; Kramer, Kim
Abstract: IMPORTANCE: Embryonal Tumor/Multilayered Rosettes (ETMR) is an aggressive, lethal, CNS tumor in young childr. B7-H3 is an inhibitory ligand for natural killer cells and T cell overexpressed in a number of embryonal tumors. 131-Omburtomab (8H9) is a radiolabeled monoclonal antibody under investigation for intraventricular administration for primary and metastatic CNS disease. We explored the use of intraventricular 131 I-8H9 targeting B7-H3 in patients with ETMR. DESIGN: Patients were enrolled in an IRB approved trial. Three symptomatic children (ages 14 months, 3 and 3.5 years) had large parietal masses confirmed to be B7-H3-reactive ETMR Patients received 2 mCi 131 I-Omburtamab as a tracer followed by 1 or 2 therapeutic 131 I-Omburtamab injections. Dosimetry was based on serial CSF, blood samplings and region of interest (ROI) on nuclear scans. Brain and spine MRIs and CSF cytology were done at baseline, 5 weeks after 131 I-Omburtamab, and approximately every 3 months thereafter. Acute toxicities and survival were noted. RESULTS: Patients received surgery, focal radiation, and high dose chemotherapy. Patients 1 and 2 received 131 I-Omburtamab (80 and 53 mCi, respectively). Patient 3 had a local recurrence prior to 131 I-Omburtamab treated with surgery, external beam radiation, chemotherapy, then 131 I-Omburtamab (36 mCi). 131 I-Omburtamab was well-tolerated. Mean dose delivered by 131 I-Omburtamab was 68.4 cGy/mCi to CSF and 1.95 cGy/mCi to blood. Mean ROI doses were 230.4 (ventricular) and 58.2 (spinal) cGy/mCi. Patients 1 and 2 remain in remission 6.5 years and 2 years after diagnosis, respectively; patient 3 died of progressive disease 7 month after therapy, 2 years after diagnosis. CONCLUSIONS: 131 I-Omburtamab appears safe with favorable dosimetry therapeutic index. When used as consolidation following surgery and chemoradiation therapy, 131 I-Omburtamab may have therapeutic benefit for patients with ETMR.